Sustaining existing and prospective passengers of urban public buses: the case study of rapid Kuantan, Pahang, Malaysia - Ponrohono, Zakiah; Bachok, Syahriah; Mohamed Osman, Mariana; Ibrahim, Mansor (SustaiN Society, 2016)
The paper introduces the various improvements implemented on buses in an eastern coastal city in Malaysia. Public buses in Malaysia, in general, and Kuantan, in particular, have been facing many challenges, including dwindling number of passengers and high costs of fleet maintenance. The research focused on the passengers’ perspective of the new provision of bus services from the aspects of frequency, affordability, safety and security as well as comfort and convenience, all being sustainable public transport indicators adopted by Malaysia. Satisfaction with the current patronage and future aspiration were also evaluated against several quality measures of these buses and the waiting facilities. In ensuring the provision was sustainable, the company operating the bus services has also introduced disabledfriendly ramps for universal accessibility and on-board static and variable message signage and graphical presentation of bus routes and bus stops. Responses have been mixed on these value-added services. The research found that some socio-demographic and trip characteristics indeed influenced the current satisfaction levels, perceived services sustainability and passengers’ expectation of future services. Improvements, hence, have been recommended to the bus operators and discussion with the management of the company has been undertaken to ensure future sustainability of Rapid Kuantan bus services.